The effect of tocopheryl phosphates on atherosclerosis progression in rabbits fed with a high cholesterol diet - KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2006)
The effect of tocopheryl phosphate on atherosclerosis progression has been studied in rabbits, fed with a 2% cholesterol diet and compared with an equivalent amount of alpha-tocopheryl acetate. The results show that the atherosclerotic-preventing effect of the phosphate derivative was more pronounced than that of the acetate derivative. alpha-Tocopheryl phosphate was also more potent in diminishing the expression of CD36 than the acetate derivative. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: tocopherol; antioxidants; atherosclerosis; tocopheryl phosphate; VITAMIN-E; GENE-EXPRESSION; PROTEIN